Smaller plants in warmer water could have implications for future Kelp forests - Thomas Wernberg; Karen Filbee-Dexter; Thibaut de Bettignies; Jean-Charles Leclerc; Dominique Davoult; Laurent Lévêque; Hartvig C. Christie; David C. Dyer; Robert J. Anderson; Mark D. Rothman; John J. Bolton; Kjell Magnus Norderhaug; et al. (Scientific Reports)
Abstract Global warming is driving contraction of species’ ranges through migration and mortality at their warm edge. However, for most species more subtle, sub-lethal changes in performance will be a more ubiquitous response to the Anthropocene. It has been suggested that reduction in body size will be a universal response to warming for cold-water species. Here we tested this hypothesis for two dominant kelp species in the northern and southern hemispheres, respectively. We tested if populations from cool and warm environments would be morphologically distinct, with warm-water populations displaying structural features indicative of sub-optimal conditions (smaller sizes). We found empirical evidence consistent with size reduction of kelp stipes, blades, and biomass of associated epiphytes from cool to warm water in both hemispheres. These changes are ecologically significant because they affect how kelps engineer their local environment, the three-dimensional habitat they create, and the associated communities they support. Reduced size of cold-water habitat forming species such as kelps may be a sublethal effect of warming that could have widespread but previously overlooked effects on the structure of ecosystems and the services that they provide.